Tuning Alginate Bioink Stiffness and Composition for Controlled Growth Factor Delivery and to Spatially Direct MSC Fate within Bioprinted Tissues. Issue 1 (December 2017) - Freeman, Fiona; Kelly, Daniel
Abstract Alginate is a commonly used bioink in 3D bioprinting. Matrix stiffness is a key determinant of mesenchymal stem cell (MSC) differentiation, suggesting that modulation of alginate bioink mechanical properties represents a promising strategy to spatially regulate MSC fate within bioprinted tissues. In this study, we define a printability window for alginate of differing molecular weight (MW) by systematically varying the ratio of alginate to ionic crosslinker within the bioink. We demonstrate that the MW of such alginate bioinks, as well as the choice of ionic crosslinker, can be tuned to control the mechanical properties (Young's Modulus, Degradation Rate) of 3D printed constructs. These same factors are also shown to influence growth factor release from the bioinks. We next explored if spatially modulating the stiffness of 3D bioprinted hydrogels could be used to direct MSC fate inside printed tissues. Using the same alginate and crosslinker, but varying the crosslinking ratio, it is possible to bioprint constructs with spatially varying mechanical microenvironments. Moreover, these spatially varying microenvironments were found to have a significant effect on the fate of MSCs within the alginate bioinks, with stiffer regions of the bioprinted construct preferentially supporting osteogenesis over adipogenesis.